2020
DOI: 10.3390/land9110457
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy Potential and Greenhouse Gas Emissions from Intensifying European Temporary Grasslands

Abstract: Agricultural intensification is considered essential for meeting growing demand for food and biomass for energy purposes. Intensifying grasslands is under-represented, although it is a promising option given their large land area and relatively low management levels. This study quantifies the bioenergy potential from intensifying temporary grasslands in Europe and the integral greenhouse gas emission effects in 2030. We first conducted a literature review of intensification options for European grasslands and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The studies conducted so far have confirmed that both perennial and annual grasses can play a key role in the implementation of lignocellulosic biomass for various energy purposes [6]. An analysis by Wicke et al [7] showed that the sustainable intensification of temporary grasslands can provide a total of 853 kha of surplus area for energy production in the European Union. Such action would allow the production of 3.7 to 11 million tonnes of dry mass of biomass, depending on the degree of use of conventional grass species and grassy energy crops, which could be tantamount to obtaining additional energy potential in the amount of 67-213 PJ•year −1 [7].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The studies conducted so far have confirmed that both perennial and annual grasses can play a key role in the implementation of lignocellulosic biomass for various energy purposes [6]. An analysis by Wicke et al [7] showed that the sustainable intensification of temporary grasslands can provide a total of 853 kha of surplus area for energy production in the European Union. Such action would allow the production of 3.7 to 11 million tonnes of dry mass of biomass, depending on the degree of use of conventional grass species and grassy energy crops, which could be tantamount to obtaining additional energy potential in the amount of 67-213 PJ•year −1 [7].…”
Section: Introductionmentioning
confidence: 90%
“…An analysis by Wicke et al [7] showed that the sustainable intensification of temporary grasslands can provide a total of 853 kha of surplus area for energy production in the European Union. Such action would allow the production of 3.7 to 11 million tonnes of dry mass of biomass, depending on the degree of use of conventional grass species and grassy energy crops, which could be tantamount to obtaining additional energy potential in the amount of 67-213 PJ•year −1 [7]. The importance of grassy biomass and its potential was also confirmed in the Biomass Policies project [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, it occupies more than a third of agricultural land, and as an ecosystem, it is characterised by its unique ecological value [1]. Grassland differs in terms of management, yield, environmental and biodiversity value and intensification measures specific to different grassland types [2]. It ranges from extensively managed semi-natural grassland with low intensity of use and high biodiversity value to intensively managed, monocultural and low biodiversity value grassland [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Grassland differs in terms of management, yield, environmental and biodiversity value and intensification measures specific to different grassland types [2]. It ranges from extensively managed semi-natural grassland with low intensity of use and high biodiversity value to intensively managed, monocultural and low biodiversity value grassland [1][2][3]. The degree of intensification, i.e., manure and fertiliser inputs, grazing pressure, cutting frequency and grassland renewal, determines the productivity of grassland but can also be considered a proxy for its biodiversity value [1].…”
Section: Introductionmentioning
confidence: 99%
“…Meerbeek et al [3] explored the biomass potential for bioenergy in the landscape beyond forests and agricultural land: gardens, roadsides, sports fields, conservation areas, etc., and stated that a large amount of biomass that is created by their regular management should not be considered as waste, but as a sustainable bioenergy resource. Wicke et al [4] quantified the bioenergy potential from intensifying grasslands in Europe. The production potential of straw harvested over agricultural consumption in Poland and its use for energy purposes were evaluated by Gradziuk et al [5].…”
Section: Introductionmentioning
confidence: 99%